Stimulation of d - and l -lactate dehydrogenases transcriptional levels in presence of diammonium hydrogen phosphate resulting to enhanced lactic acid production by Lactobacillus strain - Singhvi, Mamata S.; Zendo, Takeshi; Iida, Hiroshi; Gokhale, Digambar V.; Sonomoto, Kenji (Journal of Bioscience and Bioengineering, 2017)
The present study revealed the effect of nitrogen sources on lactic acid production and stimulation of d- and l-lactate dehydrogenases (LDH) of parent Lactobacillus lactis NCIM 2368 and its mutant RM2-24 generated after UV mutagenesis. Both the parent and mutant strains were evaluated for d-lactic acid production in control and modified media. The modified media did not show remarkable effect on lactic acid production in case of parent whereas mutant exhibited significant enhancement in d-lactic acid production along with the appearance of l-lactic acid in the broth. Both LDH activities and specific activities were found to be higher in mutant than the parent strain. These results suggested that the diammonium hydrogen phosphate in modified media triggered the expression of LDH genes leading to enhanced lactic acid production. This observation has been proved by studying the expression levels of d- and l-LDH genes of parent and mutant in control and modified media using quantitative RT-PCR technique. In case of mutant, the transcriptional levels of d-LDH and l-LDH increased ∼17 fold and ∼1.38 fold respectively in modified medium compared to the values obtained with control medium. In case of parent, no significant change in transcriptional levels of d- and l-LDH was found when the cells were grown in either control medium or modified medium. This study suggested that the mutant, RM2-24 has l-LDH gene which is expressed in presence of (NH4)2HPO4 resulting in l-lactic acid production. Co-production of l-lactic acid in d-lactic acid fermentation may be detrimental in the PLA production.